2012
DOI: 10.1016/j.ahj.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of QT prolongation using a novel electrocardiographic analysis algorithm applying intelligent automation: Prospective blinded evaluation using the Cardiac Safety Research Consortium electrocardiographic database

Abstract: Background The Cardiac Safety Research Consortium (CSRC) provides both “learning” and blinded “testing” digital ECG datasets from thorough QT (TQT) studies annotated for submission to the US Food and Drug Administration (FDA) to developers of ECG analysis technologies. This manuscript reports the first results from a blinded “testing” dataset that examines Developer re-analysis of original Sponsor-reported core laboratory data. Methods 11,925 anonymized ECGs including both moxifloxacin and placebo arms of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…As anticipated based on the comparison of the single-deltas there are almost no discernable differences in the time-profiles, with 63% of the time-points having less than 1 ms difference (86% within 2 ms) and all the confidence intervals overlap. These results are similar to numbers reported by Green et al (7 out of 11 time-points) for comparison of QT algorithms to detect effects of moxifloxacin [26]. The exposure-response relationships obtained from automated and semi-automated measurements for dofetilide and quinidine (Fig 5) and ranolazine and verapamil exhibited overlapping population predictions (Fig 6).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As anticipated based on the comparison of the single-deltas there are almost no discernable differences in the time-profiles, with 63% of the time-points having less than 1 ms difference (86% within 2 ms) and all the confidence intervals overlap. These results are similar to numbers reported by Green et al (7 out of 11 time-points) for comparison of QT algorithms to detect effects of moxifloxacin [26]. The exposure-response relationships obtained from automated and semi-automated measurements for dofetilide and quinidine (Fig 5) and ranolazine and verapamil exhibited overlapping population predictions (Fig 6).…”
Section: Resultssupporting
confidence: 86%
“…Moreover, the majority of the outliers are from two subjects near maximum concentration of dofetilide and quinidine that have extreme QTc prolongation (~80 ms) far beyond the normal level of regulatory concern (~10 ms). These results are comparable to the difference between two QT algorithms for detecting moxifloxacin effects, where a mean difference of <1 ms was observed with a SD of 9 ms [26]. Furthermore, in FDA study 2, which had less substantial QTc prolongation compared to FDA study 1, but still prolongation of ~40 ms, the average single-deltas difference were within 1 ms for all intervals with a SD of <3 ms.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Similar to the necessity of having serial ECGs interpreted by the same observer, ECG measurements by different equipment may lead to substantial variability (Kligfield et al, , ). However, since the algorithms used in the commercial equipment are steadily advancing (Green et al, ) their clinical reliability is now probably at least equivalent to fully manual measurements especially if combined with visual verifications to eliminate occasional outliers (Hnatkova et al, ).…”
Section: Consistency Of Morphological Interpretationsmentioning
confidence: 99%
“…Currently, this database includes ECGs derived from moxifloxacin (the positive control in TQT studies), placebo data sets, and the congenital long QT syndrome data submitted to CSRC . Thus far, proof‐of‐principle studies have demonstrated the value of the ECG Warehouse for developing algorithms that assess drug‐induced QT prolongation potential …”
Section: Ppp Deliverables and The Critical Path Opportunities Listmentioning
confidence: 99%